Analysis of Key Performance Indicator Report’s contribution in enhancing employee performance and sales target achievement while providing logic behind employee appraisal decision making process of Sales Department of Square Toiletries Ltd - Synthia, Anika Tabassum (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.